The role of online counseling in promoting psychological capital of students in corona isolation - Nooshin Pordelan; Samira Vakili; Hamid Heydari; Shekoofeh Khamsehzadeh; Simin Hosseinian (Shahrekord University of Medical Sciences, 2022)
Background and aims: Over the last six months, the use of technology and the internet in Iran is significantly increased due to the coronavirus pandemic. This study aimed to investigate the effect of online career counseling on students' psychological capital (i.e., self-efficacy, resilience, optimism, and hope) during corona isolation. Methods: The research design was quasi-experimental. The statistical population of this study included all students who were members of social media (i.e., WhatsApp, Telegram, Facebook, and LinkedIn). After the announcement and completion coronavirus anxiety questionnaire, 30 students who had obtained scores higher than the average level were selected and randomly assigned into experimental (15 students) and control (15 students) groups. Results: The findings showed that after the online counseling course, the intervention group outperformed the control group in psychological capital components (i.e., self-efficacy, resilience, optimism, and hope). Conclusion: According to the findings of this study, online counseling can be an effective source for career counselors, especially in developing countries. Besides face-to-face counseling, its services can help students increase their psychological capital.